The effect of toothpaste containing bacteriocin extract in the growth of streptococcus mutans in vitro - Albesa, Jean Mitchelle P.; Breva, Einnor Assiren B.; Tumang, Heherson M.
Introduction. Over the years, developments in research have geared up towards finding more preventive and less aggressive approaches against dental caries. Treatments are recently directed towards etiological agents, particularly, Streptococcus mutans. Bacteriocins have been known to inhibit bacterial growth in conditions where competition against susceptible bacteria of the same or closely-related species exists.The purpose of this study is to determine the effect of toothpaste containing bacteriocin extract on the growth of Streptococcus mutansin vitro. This study aims to show if toothpaste can deliver that effect of bacteriocin on the growth of Streptococcus mutans in vitro at a given time of exposure. If proven effective, this toothpaste could be recommended as an alternative to reduce the prevalence of dental caries.
Methods. A quantitative experimental study using a randomized complete block design (RCBD) and one-way Analysis of Variance (ANOVA) was done. Probiotic toothpaste containing bacteriocin extract as its active ingredient, and a negative control, regular non-fluoridated toothpaste, were used.
Streptococcus mutans was inoculated into a trypticase-yeast-cysteine (TYC) agar plate, incubated, and allowed to grow for 48 hours. An isolated culture was mixed into Brain Heart Infusion (BHI) broth and was incrementally added until it reached the turbidity that matched with 0.5 McFarlane's solution. Using sterile cotton swabs, TYC plates that were divided into 4 quadrants were inoculated. Six-mm filter paper disks were used to diffuse the toothpastes: 3 disks impregnated with the probiotic toothpaste with bacteriocin extract into 3 corresponding quadrants; 1 disk with regular non-fluoridated toothpaste into 1 quadrant. This set-up was done in triplicates. All plates were placed in a closed container with a lit candle inside in order to obtain an oxygen-free environment. This container was placed in an incubator set at a temperature of 37°C. After 12, 24 and 48 hours periods, the clear zones or the zones of inhibition were measured from the underside of the plate using a clear ruler.
Results: For the probiotic toothpaste, an average of 10.8 mm, 11.6 mm and 11.9 mm clear zones were observed after 12, 24 and 48 hours, respectively. A zero-mm clear zone was observed for all the controls in all three set-ups.
Conclusion: Toothpaste containing bacteriocin inhibits the growth of Streptococcus mutans. There is no significant difference on the effect, however, between the lengths of time of exposure of each sample.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Toothpaste; Bacteriocins